In Situ Quantitative Graphene‐Based Surface‐Enhanced Raman Spectroscopy. Issue 6 (16th May 2017) - Tian, Huihui; Zhang, Na; Tong, Lianming; Zhang, Jin
Abstract : Quantitative surface‐enhanced Raman spectroscopy (SERS) with ultrahigh sensitivity will significantly promote its practical application in many fields, such as environment monitoring, food safety, and drug detection. However, the challenges that remain unresolved, particularly in the low concentration levels, arise from the instability of the SERS spectra and the uncertainty of the number of detected molecules. Herein, a graphene‐based, flexible, and transparent substrate for SERS quantification is reported, wherein the 2D single‐crystalline nature of graphene promises the homogeneous adsorption of molecules, facilitating the determination of the number of molecules, the separation of molecules from metal, which ensures the stability of the Raman signals, and an internal standard for the calibration of SERS intensities. The in situ quantification of probe molecules is demonstrated in an aqueous solution down to the detection limit of 10 −8 m, and the real‐time, in situ monitoring of the release process of rhodamine B molecules, which mimics practical application, for example, the controlled release of medicine, is shown. The results open up an avenue for reliable SERS quantification for practical applications with high efficiency and low cost. Abstract : In situ Raman quantitative analysis is realized by using a graphene‐based, flexible, and transparent substrate for graphene‐based surface‐enhanced Raman spectroscopy (G‐SERS). Quantification of dye molecules in aqueous solution is studied. The real‐time, in situ monitoring of the release process of rhodamine B (RhB) molecules, which mimics practical applications, is investigated by using the G‐SERS substrate.